2020
DOI: 10.3390/brainsci10020123
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of Stereotactically Injected Human Cerebrospinal Fluid Containing Glutamic Acid Decarboxylase Antibodies into the Hippocampus of Rats on the Development of Spontaneous Epileptic Activity

Abstract: Background: The conversion of glutamic acid into γ-aminobutyric acid (GABA) is catalyzed by the glutamic acid decarboxylase (GAD). Antibodies against this enzyme have been described in neurological disorders, but the pathophysiological role of these antibodies is still poorly understood. We hypothesized that anti-GAD autoantibodies could diminish the GABA content in the slice and facilitate epileptic activity. Methods: Cerebrospinal fluids (CSF) from two patients containing anti-GAD (A and B) were injected int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Carbogen (95% O 2 , 5% CO 2 ) gassed solution serves this purpose. Good cell survival has been shown in brain tissue [48][49][50], in the Langendorff perfusion system [33,34,51], and in the organ bath [52], especially when using intestinal tissue [53] or esophageal sections [54][55][56]. One study [57] reported toxic effects of 95% O 2 in prolonged esophageal cell cultures, but these results have not been replicated [58].…”
Section: Discussionmentioning
confidence: 99%
“…Carbogen (95% O 2 , 5% CO 2 ) gassed solution serves this purpose. Good cell survival has been shown in brain tissue [48][49][50], in the Langendorff perfusion system [33,34,51], and in the organ bath [52], especially when using intestinal tissue [53] or esophageal sections [54][55][56]. One study [57] reported toxic effects of 95% O 2 in prolonged esophageal cell cultures, but these results have not been replicated [58].…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine hydroxylase (TH) and glutamate decarboxylase 67 (GAD67) are the rate-limiting enzymes for the production of excitatory and inhibitory neurotransmitters in the central nervous system [ 29 , 30 ]. The production of excitatory neurotransmitters, such as dopamine and NE in the brain, depends on TH [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The production of excitatory neurotransmitters, such as dopamine and NE in the brain, depends on TH [ 31 ]. GAD67 promotes the degradation of glutamate (Glu) and accelerates the production of inhibitory neurotransmitter γ-aminobutyric acid (GABA) [ 30 ]. Our laboratory studies and those of others have shown increased TH expression and decreased GAD67 expression in the PVN during hypertension [ 32 ] and heart failure [ 33 ], causing an imbalance between excitatory and inhibitory neurotransmitters [ 34 ].…”
Section: Introductionmentioning
confidence: 99%